Exploratory study on knowledge and frequency of consumption of processed and ultraprocessed products in university students of Peru - Mamani-Urrutia, Víctor (2022)
Background: The promotion of a healthy diet should take place at all levels, including the university community. The main objective was to explore the knowledge and frequency of consumption of processed and ultra-processed products in students of a private university in Lima-Peru. Methods: Cross-sectional, exploratory study, where a structured questionnaire was applied that collected information on 398 university students of both sexes, residents in Metropolitan Lima during the period from April to June 2019. Results: Of the total number of respondents, 50.8% study a career in Health Sciences. Most of the participants claimed to recognize a processed product (75.9%), however, only 43.4% of them gave valid examples. Regarding the term ultra-processed, only 18.1% claimed to have heard them and most of them confirmed with examples. Regarding the frequency of consumption, it was evidenced that bakery products (77.6%), cheeses (64.4%), cookies (56%), yogurts and sugary milk drinks (54.3%) and snacks (52.5%) were the most consumed in the week prior to the study. Regarding the frontal labeling, it was evidenced that 40.7% of the participants affirmed that they knew them. It was found that the main factor that influenced the dissemination of the existence of octagons (50%) was through the food industry who has already been implementing front labeling on their products that are sold for consumption. Conclusions: University students show insufficient knowledge about the differences between processed and ultraprocessed products, as well as a high frequency of consumption of these products, especially ultra-processed ones.